Nature futures for the urban century: integrating multiple values into urban management - Mansur, Andressa V. (2022)
There is an emerging consensus that the health of the planet depends on the coexistence between rapidly growing cities and the natural world. One strategy for guiding cities towards sustainability is to facilitate a planning process based on positive visions for urban systems among actors and stakeholders. This paper presents the Urban Nature Futures Framework (UNFF), a framework for scenario building for cities that is based on three Nature Futures perspectives: Nature for Nature, Nature for Society, and Nature as Culture. Our framework engages stakeholders with envisioning the three Nature Futures perspectives through four components using participatory methods and quantitative models: identification of the socio-ecological feedbacks in cities, assessment of indirect impacts of cities on biodiversity, development of multi-scale indicators, and development of scenarios. Stakeholders in cities may use this framework to explore different options for integrating nature in its various manifestations within urban areas and to assess how different community preferences result in various cityscapes and distribution of associated benefits from nature among urban dwellers across multiple scales.